Administrative Services Satisfaction Survey in Private Higher Education Institution in Malolos City, Bulacan, Philippines - Estacio, Dennis L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The study examined the level of satisfaction of the administrators, teaching and non-teaching personnel of services rendered by the Administrative Services through Survey in Private Higher Education Institution in Malolos City, Bulacan. An ongoing effort to improve the efficiency and effectiveness of programs and services in the Private Higher Education Institution in Malolos City, Bulacan and specifically to identify needed adjustments to better “facilitate education” through Administrative Services (AS), the Head, University Buildings and Campus Ground Maintenance Unit develop and administer a comprehensive Satisfaction Survey. The purpose of the study is to examine the area of strengths and weaknesses that were identified through the survey questionnaire used by 50 respondents representing the 20% of the Private Higher Education Institution in Malolos City personnel. This study makes use of the descriptive survey method to obtain date and information needed in determining the Administrative Services Satisfaction Survey. All Administrators, faculty, and non-teaching staff in the Private Higher Education Institution in Malolos City were invited by questionnaire and completed the survey. The purpose of this brief is to examine the responses from the fifty valid surveys received. The summary of the study provides recommendations for further research and to produce corrective actions on the area that need improvement.